Peran Mediasi Persepsi Kohesi Sosial dalam Hubungan Prediktif Persepsi Pemanfaatan Ruang Terbuka Publik Terhadap Kesehatan Jiwa - Nisa, Afifatun; Juneman, Juneman (UI Scholars Hub, 2012)
Various phenomena involving university students such as suicide and gang fights indicate that students mental health conditions of need to be worried about. Some studies had linked the public space utilization with social interaction facilitation and social cohesion, as well as social cohesion with mental health. The original contribution of this research is that it employed perceived social cohesion as the mediating variable of the predictive relationship between public open space utilization with mental health. The design of this research is non-experimental, predictive correlational. As many as 375 university students in Jakarta participated in this research (Mage = 20.8 years old; SDage = 1.4 years old). This research used convenience, incidental sampling technique. The path analysis showed that the perceived public open space utilization is able to predict mental health level through perceived social cohesion (χ2 = 0, df = 1, p > 0.05, RMSEA < 0.05).